DEVELOPMENT OF FORECAST MODEL FOR DOMESTIC WATER DEMAND IN HUNG NHAN TOWN, HUNG HA DISTRICT, THAI BINH PROVINCE - Thi Thuy, Tran; Xuan Dung, Bui (Journal of Forestry Science and Technology, 2017)
To determine characteristics and construct forecasting models of domestic water demand in Hung Nhan town, Hung Ha, Thai Binh, 110 households were selected randomly for interviewing and measuring from June to August, 2017. Needed information such as: number of people, number of male and female, average income was gathered in each family by interview. Besides, domestic water consumption was recorded by water meter and using water level method. The change in water level in a tank expresses daily use of water in a household. To develop forecast model of domestic water, we used linear and multiple linear regression then its reliable was test by different indices. Main findings of this study are: (1) The domestic water amount varied in different households (0.17 m³ ~ 1.17 m³) and daily water consumption of about 0.17 m³/person; (2) Four forecast models were developed. All models were statistically significant and showed a correlation between variables and domestic water demand but the one constructed based on numbers of male and female (Y3) was the most reliable with value of NSE, PBIAS, R² of: 0.904, 0.07 and 0.73 respectively, while income-based model had lowest confidence (NSE = 0.51, PBIAS = 0.18, R² = 63). These finding suggested that all factors: number of people, gender and income had a relationship with domestic water demand and should be included in the forecast model construction in order to minimize the errors.